2018
DOI: 10.1101/317115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Remote manipulation of magnetic nanoparticles using magnetic field gradient to promote cancer cell death

Abstract: The manipulation of magnetic nanoparticles (MNPs) using an external magnetic field, has been demonstrated to be useful in various biomedical applications. Some techniques have evolved utilizing this non-invasive external stimulus but the scientific community widely adopts few, and there is an excellent potential for more novel methods. The primary focus of this study is on understanding the manipulation of MNPs by a time-varying static magnetic field and how this can be used, at different frequencies and displ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…The model remarkably predicted the experimental results, showing how internalization mostly occurred in correspondence of the magnet boundary (besides some layers close to the channel side boundary, where capture was favored by slow speed, i.e., viscous effects). This is in consistent with the fact that magnetic attraction is more pronounced close to the edge of the permanent magnet due to well-known field and gradient effects [ 57 , 58 , 59 ]. Overall, the possibility to accurately model the considered dynamic targeting strategy fosters the quantitative characterization and design of related approaches, in turn supporting potential translation to more clinically-relevant frameworks in the longer term.…”
Section: Resultssupporting
confidence: 87%
“…The model remarkably predicted the experimental results, showing how internalization mostly occurred in correspondence of the magnet boundary (besides some layers close to the channel side boundary, where capture was favored by slow speed, i.e., viscous effects). This is in consistent with the fact that magnetic attraction is more pronounced close to the edge of the permanent magnet due to well-known field and gradient effects [ 57 , 58 , 59 ]. Overall, the possibility to accurately model the considered dynamic targeting strategy fosters the quantitative characterization and design of related approaches, in turn supporting potential translation to more clinically-relevant frameworks in the longer term.…”
Section: Resultssupporting
confidence: 87%
“…Similar results have been observed by other research groups [ 381 , 382 ]. In contrast, other publications have shown that as opposed to static magnetic fields, the oscillatory ones facilitate uptake and led to superior MF [ 380 , 383 , 384 , 385 ]. However, the evidence is not compelling enough to elucidate whether this is also the case for endosomal escape.…”
Section: An Overview Of Ion-mediated Transfection In Gene Editingmentioning
confidence: 86%